Testicular Epidermoid Cyst and Testis Sparing Surgery - Barut, Osman; Karakeci, Ahmet; Ozan, Tunc; Firdolas, Fatih (Derman Medical Publ, 2014)
Epidermoid cysts are rare benign testicular lesions and pathogenesis are still controversial. In this case we presented a 39-year-old patient with testicular epidermoid cyst which testis-sparing surgery was performed. Pathogenesis, diagnostic criteria, differential diagnosis and treatment options of the disease are discussed.
Keywords: Testicular Tumors; Epidermoid Cysts; Testis-sparing Surgery